Partial tetrasomy 11q resulting from an intrachromosomal triplication of a 22 Mb region of chromosome 11. Issue 4 (22nd March 2017) - Kekis, Mariana; Deeg, Carol; Hashimoto, Sayaka; McKinney, Aimee; Erdman, Linda; Green‐Geer, Cecelia; Shuss, Christine; Hickey, Scott; Astbury, Caroline; Pyatt, Robert E.
Abstract : Intrachromosomal triplications are complex chromosomal rearrangements which arise during meiosis or mitosis and lead to a tetrasomic dose of the affected genomic regions. We describe a female patient harboring an intrachromosomal triplication who presented to the Genetics clinic with dysmorphic features, including telecanthus, flat facial profile, and prognathism, short stature, widely spaced nipples, multiple allergy complaints, loose bowel movements, and mild speech delay. Microarray analysis showed a copy number gain of a 22.37 Mb region of chromosome 11 between bands 11q14.1 and 11q22.1. This region contains 95 genes and seven microRNAs, none of which have been implicated in a disease resulting from increased gene dosage. FISH analysis using a probe targeted to the middle of the segment of the copy number gain yielded a pattern indicative of a tetrasomy via an intrachromosomal triplication, with three signals on the long arm of one homologue of chromosome 11 and the fourth on the other homologue. Subsequent FISH analysis showed that the middle triplicated fragment was positioned in an inverted orientation relative to the outer fragments. To investigate the mechanism by which the intrachromosomal triplication occurred, SNP microarray analysis was performed. These results were consistent with the presence of multiple haplotypes in the tetrasomic region and suggest that the intrachromosomal triplication in our patient arose in one parent during meiosis. © 2017 Wiley Periodicals, Inc.